Cavitation dynamics and flow aggressiveness in ultrasonic cavitation erosion. (15th August 2021) - Du, Jianhua; Chen, Fengjun
Highlights: The flow dynamics and aggressiveness under ultrasonic cavitation are modeled by CFD. The improved model contains the bubble dynamics and the temperature-dependent Tait equation of state. The primary collapse determines the circular cavitation erosion region. The secondary collapse causes an annular region with the greatest depth. Abstract: The mechanisms of cavitation erosion have been the subject of numerous studies, but the cavitation dynamics and flow aggressiveness thereby produced are less known. We develop a new numerical model to capture the cavity evolution and pressure pulsation, which are related to cavitation erosion. The source term in the interphase mass transfer model is obtained from Rayleigh–Plesset equation under the acoustic field. Mathematical closure is achieved by the temperature-dependent Tait equations of state to apply to the cavitation. The comparison with the measurement results of ultrasonic cavitation shows that the model has a good predictive ability in cavity evolution, cavity volume and pressure pulsation. The surface erosion pattern is attributed to concentrated pressure. Given the shielding effect of the central bubble, the pressure is concentrated on the edge, resulting in an annular region with the greatest depth. The cavity characteristics are gap-dependent. When the gap height is 1.0 mm, cavitation erosion is the most serious. The size of the erosion area is determined by the maximum bubble number density on the sample surface. Graphical abstract: Image, graphical abstract